Інтелектуальна модель ідентифікації ваги великої рогатої худоби - Черкасов, А. Д. (ХНУРЕ, 2025)
This paper explores the development and optimization of an intelligent weight identification system for agricultural animals. The study emphasizes the significance of accurate weight measurement for assessing the health and productivity of livestock such as cows and pigs. A novel model is proposed that utilizes non-contact measurement techniques based on 3D imaging and neural networks for weight estimation. This method ensures precise measurements without causing stress to the animals, which is critical for maintaining their health and performance. Experimental results demonstrate the feasibility of the proposed system for improving efficiency in farming operations and contributing to the agricultural industry overall productivity.
Keywords: ідентифікація ваги; рогата худоба